Fostering EYL’s Critical Literacy Skills Using the Four Resources Model in Folklore - Islamy, Jiaul Haque; Setyarini, Sri; Gustine, Gin Gin (Universitas Galuh, 2025)
Literacy instruction is frequently restricted to word decoding and literal meaning understanding in many EFL contexts, especially in early education. This study addresses the necessity of shifting towards critical literacy methods that enable young learners to engage with texts from a variety of perspectives. The aim of this research is to investigate how the Four Resources Model by Luke and Freebody (1999) can be applied to develop critical literacy skills in English Young Learners (EYL) through the use of folklore as a learning medium. The study, which used a qualitative case study methodology, was carried out in an Indonesian seventh-grade classroom. Semi-structured interviews and classroom observations were used to gather data. The results show that combining culturally relevant folktales with the Four Resources Model-code breaker, text participant, text user, and text analyst improved students' vocabulary, grammatical awareness, and capacity to consider the social values and ideologies expressed in texts. The study shows that with the help of organised, context-rich training, young students can go from basic comprehension to critical interpretation.